Remote hearing aid fitting: Tele-audiology in the context of Brazilian Public Policy - Penteado, Silvio Pires; Ramos, Sueli de Lima; Battistella, Linamara Rizzo; Marone, Silvio Antonio Monteiro; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2012)
Introduction: Currently, the Brazilian government has certificated nearly 140 specialized centers in hearing aid fittings through the Brazilian National Health System (SUS). Remote fitting through the Internet can allow a broader and more efficient coverage with a higher likelihood of success for patients covered by the SUS, as they can receive fittings from their own homes instead of going to the few and distant specialized centers.Aim: To describe a case of remote fitting between 2 cities, with revision of the literature.Method: Computer gears, a universal interface, and hearing aids were used. Case study: An audiologist located in a specialized center introduced a new hearing aid and its fitting procedure to a remote center (200 km away). The specialized center helped the remote center in fitting a hearing aid in 2 patients, and performed fitting in one of its own patients. The whole process was done through the Internet with audio and video in real time.Results: Three patients were fitted remotely. Three audiologists were remotely trained on how to fit the hearing aids.Conclusions: Remote fitting of hearing aids is possible through the Internet, as well as further supplying technical training to a remote center about the fitting procedures. Such a technological approach can help the government advance public policies on hearing rehabilitation, as patients can be motivated about maintaining their use of hearing aids with the option to ask for help in the comfort of their own homes.
Keywords: public policies; hearing aids; telemedicine; internet; technological development; biomedical engineering